The social contract and refugee protection: A comparative study of Turkey and Germany in the 1990s - David McKeever (Transformation, Integration and Globalization Economic Research (TIGER), 2005)
This paper hopes to challenge the existing paradigm in refugee studies, which presents the development of domestic asylum policies as being essentially driven by a conflict between international humanitarian norms and the self-interest calculations of sovereign states. This paper will show that asylum policies are determined more by conflicting domestic principles, and that the dominance of one or another of the competing domestic principles is decided largely by the prevailing 'social contract' notions held by the state. That is, notions about social contract determine what the perceived obligations and priorities of the state are; this 'hierarchy of obligations' is clearly manifested in, and indeed guides the development of, asylum policies. Looking first at the macro level, the paper outlines some of the important philosophical dimensions of the social contract idea, some possible variations, as well as the role of the social contract in international refugee and human rights law. Moving on to the chosen case studies, the second half of the paper examines the dominant notions of 'social contract' in Turkey and Germany, and highlights some of the many ways these notions impacted upon refugee protection in each country during the 1990s. Finally, the paper compares and contrasts briefly some of the themes and processes which emerged in the two case studies, and concludes by evaluating these results in light of the existing refugee studies paradigm.
Keywords: 330; Migrationspolitik; Flüchtlinge; Menschenrechte; Asylrecht; Türkei; Deutschland; Sozialvertrag; Internationales Recht